Current knowledge of Holothuriida (Holothuroidea: Echinodermata) from Brazil - Prata, Jéssica; Christoffersen, Martin Lindsey (Frontiers in Marine Science, 2024)
Sea cucumbers are the second most diverse class among echinoderms. They are characterized by an elongated body and dermal ossicles in the body wall. Among the included groups in that class, the order Holothuriida encompasses many species of commercial interest. Faced with the threats of biodiversity loss resulting from the climate crisis and the advancement of cities, this study provides an overview of recent research involving the Holothuriida of the Brazilian Coast. Searches were carried out in the main periodical databases, using appropriate keywords, targeting publications on the subject in the period between 2000 and 2023. In total, 69 publications were found, most of them corresponding to scientific articles in international journals. Most of the studies come from the Northeast region in Brazil (56.52%). Regarding lines of research, those involving taxonomy and molecular analysis were the most prevalent. Over these 20 years, seven species constituted new occurrences. Of note are the studies focused on Holothuria (Halodeima) grisea, which makes up 39.13% of papers. Despite progress, little is known about morphological variations, genetic distance between populations, population densities, and on reproductive biology of species. Brazil has a vast, heterogeneous coastal area, with unique characteristics to which the species are adapted. The findings reinforce the importance to expand studies aiming on knowing the biodiversity, reproductive biology, and population densities of species. Such data are essential for the creation of public policies aimed at the conservation of species of Holothuriida and their habitats.